A set of clinical and laboratory markers differentiates hyper-IgE syndrome from severe atopic dermatitis - ÖZEN, AHMET OĞUZHAN; KOLUKISA, BURCU; AYDINER, ELİF; BARIŞ, SAFA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Hyper-IgE syndrome (HIES) patients may share many features observed in severe atopic dermatitis (SAD), making a diagnostic dilemma for physicians. Determining clinical and laboratory markers that distinguish both disorders could provide early diagnosis and treatment. We analyzed patients (DOCK8 deficiency:14, STAT3-HIES:10, SAD:10) with early-onset SAD. Recurrent upper respiratory tract infection and pneumonia were significantly frequent in HIES than SAD patients. Characteristic facial appearance, retained primary teeth, skin abscess, newborn rash, and pneumatocele were more predictable for STAT3-HIES, while mucocutaneous candidiasis and Herpes infection were common in DOCK8 deficiency, which were unusual in SAD group. DOCK8-deficient patients had lower CD3(+) and CD4(+)T cells with a senescent phenotype that unique for this form of HIES. Both DOCK8 deficiency and STAT3-HIES patients exhibited reduced switched memory B cells compared to the SAD patients. These clinical and laboratory markers are helpful to differentiate HIES from SAD patients.
Keywords: Hyper-IgE syndrome; DOCK8 deficiency; STAT3 deficiency; Severe atopic dermatitis; DOCK8 DEFICIENCY; STAT3 MUTATIONS; COMBINED IMMUNODEFICIENCY; SIGNAL TRANSDUCER; GUIDELINES; PHENOTYPE; DEDICATOR; ACTIVATOR; FEATURES; DISEASE